ADEQUACY OF TREATMENT RECEIVED BY PRIMARY CARE PATIENTS WITH ANXIETY DISORDERS. Issue 5 (4th November 2013) - Weisberg, Risa B.; Beard, Courtney; Moitra, Ethan; Dyck, Ingrid; Keller, Martin B.
<x xml:space="preserve">Abstract</x> Background We examined the adequacy of pharmacotherapy and psychotherapy received by primary care patients with anxiety disorders over up to 5 years of follow‐up. Method Five hundred thirty‐four primary care patients at 15 US sites, who screened positive for anxiety symptoms, were assessed for anxiety disorders. Those meeting anxiety disorder criteria were offered participation and interviewed again at six and 12 months postintake, and yearly thereafter for up to 5 years. We utilized existing definitions of appropriate pharmacotherapy and created definitions of potentially adequate psychotherapy/cognitive‐behavioral therapy (CBT). Results At intake, of 534 primary care participants with anxiety disorders, 19% reported receiving appropriate pharmacotherapy and 14% potentially adequate CBT. Overall, 28% of participants reported receiving potentially adequate anxiety treatment, whether pharmacotherapy, psychotherapy, or both. Over up to five years of follow‐up, appropriate pharmacotherapy was received by 60% and potentially adequate CBT by 36% of the sample. Examined together, 69% of participants received any potentially adequate treatment during the follow‐up period. Over the course of follow‐up, primary care patients with MDD, panic disorder with agoraphobia, and with medicaid/medicare were more likely to receive appropriate anxiety treatment. Ethnic minority members were less likely to receive potentially adequate care. Conclusions Potentially adequate anxiety treatment was rarely received by primary care patients with anxiety disorders at intake. Encouragingly, rates improved over the course of the study. However, potentially adequate CBT remained much less utilized than pharmacotherapy and racial‐ethnic minority members were less likely to received care, suggesting much room for improved dissemination of quality treatment.